Fostering Awareness of Integrating Education for Sustainable Development in Teacher Education Institutions across the Caraga Region, Philippines - Flores, Grace T. (International Journal of Membrane Science and Technology, 2023)
This study investigates the awareness and integration of Education for Sustainable Development (ESD) within teacher education institutions in the Caraga Region, Philippines. Examining policy, legal foundations, and the ESD framework, findings reveal diverse levels of awareness regarding ESD policies and legalities, indicating the necessity for comprehensive dissemination. ESD framework integration spans social, environmental, and economic dimensions, with practices exhibiting an initial stage of adoption. Student participation in institutional decision-making varies, indicating room for enhancing inclusivity and shared governance. While environmental sustainability efforts encompass energy efficiency, challenges in eco-friendly practices and aesthetic learning environments persist. Economic empowerment through ESD is evident, when students engage in commerce-focused learning initiatives. Faculty development emerges as crucial, shaping effective ESD integration through enhanced pedagogical strategies. In summary, this study underscores the evolving landscape of ESD integration, emphasizing the importance of knowledge dissemination, student engagement, faculty development, and comprehensive sustainability initiatives within teacher education institutions. These insights contribute to holistic educational approaches, fostering environmentally aware, socially responsible, and economically equipped graduates prepared for sustainable future challenges.